2020
DOI: 10.3390/microorganisms8020238
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lactic Acid Bacteria During Pikeperch (Sander lucioperca) Larval Rearing

Abstract: This trial tested the use of lactic acid bacteria (LAB) on pikeperch (Sander lucioperca) larvae during their first feeding. The trial included the use of two probiotic treatments and one control (no probiotics). Pikeperch larvae were exposed to LAB as follows: (1) the live feed (Treatment 1, live feed) or (2) via the live feed and the larval rearing water (Treatment 2, probiotic). Significant differences were found between the treatments in terms of total length (TL), myomere height (MH), overall survival, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…As reported by several recent studies (Imentai et al, 2019;Yanes-Roca et al, 2018;Yanes-Roca, Leclercq, et al, 2020), pikeperch is a species that has a high dependence on rotifers and may have a high susceptibility for taurine deficiency since rotifers have very low taurine concentrations when compared to Artemia and copepods, as described in California yellow tail (Seriola lalandi) (Hawkyard et al, 2014(Hawkyard et al, , 2015(Hawkyard et al, , 2016.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As reported by several recent studies (Imentai et al, 2019;Yanes-Roca et al, 2018;Yanes-Roca, Leclercq, et al, 2020), pikeperch is a species that has a high dependence on rotifers and may have a high susceptibility for taurine deficiency since rotifers have very low taurine concentrations when compared to Artemia and copepods, as described in California yellow tail (Seriola lalandi) (Hawkyard et al, 2014(Hawkyard et al, , 2015(Hawkyard et al, , 2016.…”
Section: Discussionmentioning
confidence: 95%
“…In this sense, great progress has been made in improving the efficiency and reducing the high costs of pikeperch culture in RAS as it is widely accepted that the commercial development of this species relies on the optimization of recirculation culture techniques (FAO, 2016;Steffens et al, 1996). In an effort to meet such an objective, the introduction of rotifers during first feeding has contributed to improved larval quality, survival and growth (Imentai et al, 2019(Imentai et al, , 2020Yanes-Roca et al, 2018;Yanes-Roca, Leclercq, et al, 2020;Yanes-Roca, Mráz, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such nutritional value enhancement has a direct effect on growth, functional development, stress resilience, and survival rate, as shown in several species such as barramundi (Lates calcarifer), seabream (Sparus aurata), seabass (Dicentrarchus labrax), and pikeperch (Ferreira et al, 2018;Nyina-wamwiza et al, 2005;Thépot et al, 2016;Yanes-Roca, Leclercq, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although Artemia is a common diet in fish larviculture, the nutritional profile, size and inconsistent in biochemical composition, makes it less suitable candidate for first feeding. In this respect, recent studies showed the importance of larval first feeding with rotifers (Brachionus plicatilis) with a supplementation of microalgae to provide a better growth and higher survival (Yanes-Roca et al, 2018;Imentai et al, 2020;Yanes-Roca et al, 2020a;Yanes-Roca et al, 2020b). It was reported that higher growth and survival was reached when larvae fed with B. plicatilis at the beginning of exogenous feeding and afterwards replaced with Artemia or a combination of two during first feeding (Imentai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%